Application of Flexible Budget Based on Company Profit Model: Taking VK's Financial Data as an Example (Asian Business Research, 2022)
There are many types of budgeting, and budgeting based on profit models is rare. This paper combines financialbig data with management accounting methods to build a profit model in financial big data; and uses model dataas the basis and basis for preparing flexible budgets, making budget preparation and execution more scientificand feasible; The company’s budget preparation method has been introduced; more importantly, financialaccounting and management accounting are integrated, and the forecasting and budgeting functions ofmanagement accounting applications are really brought into play and applied.